Cardiovascular health awareness and the effect of an educational intervention on school-aged children in a rural district of India - Ray, Madhab (Indian Heart J, 2016)
BACKGROUND AND OBJECTIVES: India is the second most populous country in the world and two-thirds of its population is less than 35 years old. This survey was conducted to assess the level of health awareness of cardiovascular disease in adolescent school-aged children 14–16 years old, with the goal of establishing school-based health education and development of heart-healthy lifestyle practices. METHODS: A school-based survey was conducted in the rural district of West Midnapore, India between June and July of 2014. This involved a pre-evaluation of cardiovascular disease (CVD) health awareness, a short presentation on CVD, and a post-evaluation of CVD health awareness. RESULTS: A total of 2995 students (48% response rate) from 20 schools participated in the survey. The mean age of the students in the study sample was 14.7 years, 46% were male, 53% were in the 9th grade, and the rest were in the 10th grade. After assessing students’ awareness in six domains with 20 multiple-choice questions with a maximum score of 100, the mean pre-test score was 41.1 (SD ± 10.5) and the mean post-test score was 48.1 (SD ± 16.9) (p < 0.001). CONCLUSIONS: Awareness of CVD and its risk factors was far from optimal among the adolescent school-aged children in this study. A school-based educational program may help improve awareness of CVD and reduce the future disease burden in the community. The results of this study may be useful in formulating a nationwide school health program to deal with the emerging epidemic of CVD in countries such as India.